A theoretical framework of Interracial Couple Relationship Success: empirical findings from a sample of Black-White couples in the United States - Deitz, Sharon Luu (Kansas State University, 2016)
The current study proposes a theoretical model of Interracial Couple Relationship Success and empirically tests a portion of the model in which ethnic identity is linked to relationship satisfaction for Black-White interracial couples. Data were collected from 185 heterosexual Black-White marital couples in the United States. An actor-partner interdependence model (APIM) was used to test the direct and indirect effects of ethnic identity to relationship satisfaction via self-esteem and problem-solving skills. The results indicated ethnic identity of both Black and White partners was related to Black but not White partners’ self-esteem. Findings also revealed significant indirect pathways from Black partners’ self-esteem to their own relationship satisfaction via effective problem-solving skills. The indirect pathway from Black partners’ self-esteem to partner relationship satisfaction was also mediated by partner perceptions of problem-solving in the relationship. The results of this study informs the continued development of the of Interracial Couple Relationship Success model and offers data regarding the role of identity and individual well-being in the context of interracial relationships.
Keywords: interracial couples; ethnic identity; actor-partner interdependence model